An elderly man presented with autoimmune haemolytic anaemia- a consequence of severe corona virus disease 19 (COVID-19) - Hasan, Md Nazmul; Sami, Chowdhury Adnan; Amin, Md Rasul; Khan, Abed Hussain; Biswas, Sunil Kumar (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
Autoimmune hemolytic anaemia (AIHA) can be caused by many diseases like connective tissue disease, lymphoproliferative disorder, certain infections and various medications. The coronavirus disease 19(COVID-19) can cause an increased risk of thrombosis. But, the association of AIHA with COVID-19 is not well understood. Here, in this case report a 45-year-old man who presented with fever, cough, anaemia and splenomegaly. On further investigation, he was confirmed as severe COVID-19 case with AIHA. Subsequently he was managed with prednisolone with good results. BSMMU J 2021; 14 (COVID -19 Supplement): 57-59